Evaluation of eight commercial dog diets. (2014) - Daumas, Caroline; Paragon, Bernard-Marie; Thorin, Chantal; Martin, Lucile; Dumon, Henri; Ninet, Samuel; Nguyen, Patrick
Abstract: Estimation of the quality of commercial diets is a topic of interest for the majority of dog owners. Recently, in a French consumer association magazine, an evaluation of eight dog commercial dry diets (from super-premium, basic-nutrition, private-label and economy brands) according to several nutritional criteria was published. The aims of the study were: (1) to evaluate the apparent digestibility of these diets; (2) to score these diets according to digestibility results; and (3) to compare these data with the scoring of the magazine. Six adult Beagle dogs were enrolled for the digestibility trials. Diets were scored according to energy, crude protein and crude fat (CF) apparent digestibility coefficients, digestible protein-to-energy ratios and ash content. Each of the five criteria was scored from 4 to 20 points. The ranges of crude protein, CF, crude fibre and ash content were 20·9–30·6 %, 6·8–19·7 %, 2·2–3·3 % and 4·6–9·7 % on a DM basis, respectively. The ranges of energy, crude protein and CF apparent digestibility coefficients were 72·6–87·7 %, 70·4–82·5 % and 76·1–95·4 %, respectively. The range of the protein-to-energy ratio was 10–14 digestible crude protein per MJ metabolisable energy. Little overlap in the scoring systems was found, but the private-label brand and economy brand diets presented the lowest scores in the two systems. These results showed that the evaluation of commercial diets should take into account multiple nutritional aspects. In particular, analytical and biological (digestibility) criteria should be considered as complementary in the evaluation of dry dog commercial diets.